Current evidence for outcomes of free-flap reconstruction in factor V Leiden patients - Isobel Yeap; Chris Ahn; Stuart Hoffman; Rowan Gillies; John Vandervord (Australasian Journal of Plastic Surgery)
**Background**: Factor V Leiden is the most common form of inherited thrombophilic syndrome, affecting 5 per cent of Caucasians. While increased rates of venous thromboembolic complications have been regularly reported in factor V Leiden patients, little is known about their risk of microvascular complications or flap failure rates in free-flap surgery. The aim of this review is to qualitatively review the published literature on outcomes of free-flap surgery in patients with factor V Leiden. **Methods**: MEDLINE®, PubMed, EMBASE and Cochrane were searched from their dates of inception to March 2017. Nine studies of level IV evidence were included in this qualitative review. In total, these studies included 22 patients who underwent 24 free-flap operations. **Results**: Nine flap failures were reported due to thrombotic complications. Even heterozygous factor V Leiden patients had a relatively high risk of free-flap failure (3/15 free flaps), and patients who were heterozygous for factor V Leiden and had other coexistent thrombophilias had an even higher failure rate (5/6 free flaps). However, the small sample size across the nine studies, as well as the inevitable publication bias, means that definitive conclusions cannot be drawn. **Conclusion**: Despite factor V Leiden being a relatively common condition in Australia, current evidence for outcomes of free-flap reconstruction in this patient population is lacking.